Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Taboada Dusek, Gabriela Stephanie (2018)
The analysis of the company and market has been made out of different sources of information, such as the Harvard Business School’s case entitled “Fast Retailing Group” (713 – S21), prepared by Hirotaka Takeuchi, which was provided from the Universidad de Lima. Other sources were also employed such as current information published on Fast Retailing’s web site, business related articles and news from digital sources, and information from books about business administration concepts.